STRATEGI PENGEMBANGAN KEPARIWISATAAN DI DESA NUCA MOLAS SEBAGAI DESTINASI UNGGULAN DI KABUPATEN MANGGARAI - Rudiyanto, Roseven; Fanggidae, Linda Welmintje; Jerobisonif, Aplimon; Maromon, Rifat Yoktan Y.; Dima, Thomas Kurniawan; Dahoklory, Lodwik Obed (Jurnal Pariwisata Bisnis Digital dan Manajemen, 2025)
Nuca Molas Village in Manggarai Regency has strong tourism potential but does not yet have a clear development strategy. This study aims to explore its potential and propose a strategy to make Nuca Molas Village a leading destination in Manggarai Regency. The approach used in this study is qualitative. The data collection techniques are interviews, observations, and documentation. Informants were selected using purposive sampling techniques, reaching seven people. This study identified four main potentials: Natural and cultural attractions, including biodiversity and shipbuilding traditions; Accessibility, because of its location close to Wae Rebo and Labuan Bajo; Amenities, with accommodation and culinary businesses in Dintor, the crossing point to Nuca Molas; and Tourism market, which benefits from tourist visits to Labuan Bajo and Wae Rebo. The strategy must prioritize increasing accessibility, infrastructure development, partnerships, community training, and reactivating tourism awareness groups (Pokdarwis). In addition, integrating tourism products with Wae Rebo and Labuan Bajo can increase visibility and attract more visitors. This research can provide an overview of the development strategy of tourist villages, especially marine tourism. It can be used as a basis for designing tourism development in Nuca Molas Village.